2017
DOI: 10.1016/j.eururo.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Membranous Urethral Length Measurement and Continence Recovery Following Radical Prostatectomy: A Systematic Review and Meta-analysis

Abstract: Context Membranous urethral length (MUL) measured prior to radical prostatectomy (RP) has been identified as a factor that is associated with the recovery of continence following surgery. Objective To undertake a systematic review and meta-analysis of all studies reporting the effect of MUL on the recovery of continence following RP. Evidence acquisition A comprehensive search of PubMed, EMBASE, and Scopus databases up to September 2015 was performed. Thirteen studies comprising one randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
172
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 43 publications
11
172
2
8
Order By: Relevance
“…Many factors have been suggested to explain some of the variation in symptoms of PPI. These include pre‐ and post‐surgical urethral length, prostate volume at time of surgery, age, denervation, BMI, and urethral stricture . Recent reviews have concluded that there is limited evidence to support the relationship between any one of these factors and incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been suggested to explain some of the variation in symptoms of PPI. These include pre‐ and post‐surgical urethral length, prostate volume at time of surgery, age, denervation, BMI, and urethral stricture . Recent reviews have concluded that there is limited evidence to support the relationship between any one of these factors and incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…There is insufficient evidence to propose an exact cut‐off value. A recent meta‐analysis has shown that every extra millimeter of MUL is associated with 9% greater odd for return to continence . It is considered that an increased MUL could result in a greater amount of smooth muscle fibers and rhabdosphincter preservation potentially increasing the length of the urethral pressure profile and gaining muscle volume for postoperative training …”
Section: Discussionmentioning
confidence: 99%
“…Third, although the model controls for major predictors of urinary incontinence after surgery, it is possible that residual unmeasured confounding exists. Longer membranous urethral length, for example, has been associated with improved continence outcomes after RALP (24). We did not routinely perform magnetic resonance imaging for all patients and, therefore, we cannot assess the extent to which this may have affected the results.…”
Section: Discussionmentioning
confidence: 99%